2020
DOI: 10.18203/issn.2455-4510.intjresorthop20205557
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on orthopedic surgeon in Pakistan

Abstract: <p><strong>Background:</strong> The objective of our study is to assess the impact of COVID-19 pandemic on clinical practice as well as psychological impact on orthopedic surgeons of Pakistan.</p><p><strong>Method</strong>: An online survey involving orthopedic surgeons through social media platforms like WhatsApp and Facebook and also through email, to assess the impact of COVID-19 pandemic. Our survey also aims to evaluate their state of mind and physical as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There is no doubt that the pandemic resulted in an unprecedented challenge to the health care services including putting significant pressure on staff of all specialties [1]. However, the vast majority of publications on orthopaedic surgeons has focussed on the intuitive negative aspects [5][6][7][8][9][10][11]; nevertheless, any experience may also have a positive impact. The aim of this study was to collate the positive experiences reported by orthopaedic surgeons to identify important lessons for our future practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that the pandemic resulted in an unprecedented challenge to the health care services including putting significant pressure on staff of all specialties [1]. However, the vast majority of publications on orthopaedic surgeons has focussed on the intuitive negative aspects [5][6][7][8][9][10][11]; nevertheless, any experience may also have a positive impact. The aim of this study was to collate the positive experiences reported by orthopaedic surgeons to identify important lessons for our future practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the negative effects of the pandemic have been previously reported in several publications pertaining to orthopaedic surgeons [5][6][7][8][9], the aforementioned positive changes brought to our orthopaedic practice by the pandemic have not been precisely recorded. Therefore, the rationale for this study is to conduct a global survey to record those positive experiences during the pandemic specifically for orthopaedic surgery, and thus capture the new ideas, perceptions and lessons learned which in turn can be used to promote future innovation and improvement in our everyday practice of orthopaedics.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study displays outcomes of surgical management of colorectal cancer 6 . Publications are evident on experiences and challenges in different specialties, e.g., pediatric surgery, 7 breast surgery 8 , orthopedics 9 , operating department practitioners, 10 and many others.…”
Section: Introductionmentioning
confidence: 99%